Komposisi Kumbang (Coleoptera) Permukaan Tanah di Perkebunan Kelapa Sawit (Elaeis guineensis Jacq.) Rakyat Kanagarian Kunangan Parik Rantang Kabupaten Sijunjung - Risdawati, Fauzia; Dahelmi, Dahelmi; Zeswita, Armein Lusi (Pendidikan Biologi, 2013)
ABSTRACT Beetles (Coleoptera) act as a biological pest control and as recast organic matter in the forest. Changes in forest conditions in Kanagarian Kunangan Parik Rantang into oil palm plantation area is expected to affect the people of the land surface of the animals. This study aims to determine the composition of beetles (Coleoptera) in the soil surface oil of palm (Elaeis guineensis Jacq.) (Station I) and forest around the oil palm plantations of the people (Station II). This study was carried out from May to April 2013 and sampling was conducted on 12 untill 15 March 2013. Sampling was done by using pitfall traps (total of 50 pitfall traps) at both stations. The results showed that 13 genera that belong to 11 families  were found. At station II was found 12 genera and 9 families. Climatic factors and physical- chemistry at the station I and station II were measured where air temperature ranged from29.080C-31.330C, soil temperature (230C-240C), air humidity ranged from  53.17%-59.83%, soil pH from 6.6-6.7, soil moisture content from 30.45%-39.45%, and soil organic carbon content was 6.49%-7.50%. Spearman correlation analysis showed that there are differences in the composition of the genera of beetles (Coleoptera) ground level between the two stations.